Women Farmers: The First Witnesses. Issue 2 (December 2018) - Jodha, Vijay S.
This photo essay captures the personal tragedy of women farmers in a large-scale and an ongoing agrarian crisis in India that has claimed over 300, 000 lives by way of farmer suicides since 1995.